ISLAM, NEGARA DAN HAK-HAK MINORITAS DI INDONESIA - Hasan, Hasbi (Universitas Islam Negeri Raden Intan Lampung, 2012)
The widespread of shari’a by-laws in some regencies and many cases of discrimination and persecution of certain religious sects empirically are the manifestation of hegemony of majority over those of minorities which has often been overlapped with agenda and interests of political elites and the ruling power. This paper describes a number of problem concerning the majority-minority relations in Indonesia, by tracing the historical roots of resolution on such cases in Medina Charter as the constitution of Islam and the 1945 Constitution as the Constitution of Indonesia. By using descriptive-analytic approach, the author asserts that various forms of rejection and humiliation against religious minorities, both within the same religion as well as between different religions that takes places of the current is clearly in contrast to the spirit of Medina Charter and the 1945 Constitution. Facing such problem of religious majority-minority relations and their excesses and the reality of pluralism, state, in accord with the author’s conclusions, must take a dual role: The role of prevention in terms of keeping in harmony the relations between people of different religions/faiths, and of promotive one in implementing and advancing the noble universal values that favored by each religion.